Immunohistochemical assessment of HER2 expression in gastric cancer in a cohort of 118 Brazilian patients - Juliana Elizabeth Jung; Sérgio Ossamu Ioshii (Sociedade Brasileira de Patologia Clínica, 2013)
INTRODUCTION: Recent studies indicate a role of human epidermal growth factor receptor type 2 (HER2) in the development of numerous types of human cancer, including gastric cancer, and its overexpression correlates with poor prognosis and increased aggressiveness of this neoplasm. OBJECTIVES: Identify and evaluate the immunohistochemical expression of HER2 in gastric cancer from biopsies, surgical resection specimens, lymph node metastasis and distant metastasis, and evaluate their correlation with currently known clinical and histopathological prognostic factors. METHODS: Samples from 118 patients of both sexes and all age groups diagnosed with gastric cancer were analyzed. Immunohistochemistry (IHQ) was performed using the HER2 antibody, and its evaluation was made according to the modified gastric cancer testing protocol, taking into account incomplete basolateral staining or only lateral staining. RESULTS: HER2 expression did not correlate with any histological prognostic factors or clinical outcome, except for the N stage. By comparing the HER2 expression in biopsies, surgical specimen, lymph node and metastasis, 88.1% were in agreement. CONCLUSION: As anti-HER2 therapies are becoming the standard of care in gastric cancer, currently available data indicate that IHQ should be used as the screening test, and the pathologist has an important role to ensure an accurate testing of HER2 status in these tumors. In addition, the HER2 status can be tested using the available samples from biopsies, surgical specimens, nodal and extranodal metastatic disease.